THE VALUES OF KI HADJAR DEWANTARA’S CRITICAL EDUCATION: FUNDAMENTAL CONCEPT OF ACCOUNTING EDUCATION OBJECTIVE - Bakhtiar, Yohan; Triyuwono, Iwan; Irianto, Gugus (The International Journal of Accounting and Business Society, 2015)
This article analyzesthe currentofaccounting educationreality and founds a relevance values that ​​brought by modern accounting with Ki Hadjar Dewantara’s thinking. Additionally, this article explores the values ​​of Ki Hadjar Dewantara’s critical education as aformulation for basic concept of accounting education objective. Islamic spiritual value, moral value​​and freedomvalue which become the findings in this article are still a conceptual framework that requires ongoing study to obtain indicators of each value in order to formulate the concept ofaccounting education objectivesin accordance with character and identity of Indonesian people. Keywords:Ki Hadjar Dewantara, Values, Accounting Education.